Optimization of Extraction Solvent for High-performance Thin-layer Chromatography for detection of adulterants in Valerianae radix - Siddiqui, Nadeem (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Quality control of valerian represents a major concern in the pharmaceutical industry due to the huge variety of these species and their almost daily new scientific findings. Objective: The aim of the study was to investigate the sensitivity of FTIR spectroscopy for the detection of adulterated Valerianae radix and the optimization of a solvent extraction method for high-performance thin-layer chromatography (HPTLC) fingerprinting. Material and Methods: Radix valerian medicinal plant adulterant was measured by FTIR spectroscopy. The obtained data were evaluated using SIMCA (soft independent modeling of class analogies) to determine the detection limits for the undesired adulterants when systematically mixing their spectra with a data set comprising 50 batches of valerian root samples and the HPTLC system was utilized to evaluate a series of ultrasound extraction experiments. Optimal solvent composition consisting of methanol, water, and dichloromethane is used for which the flavonoid fingerprint is determined. Results: With regard to the chemometric analysis of the FTIR spectra, we found that for this particular dataset, the overall detection rates computed from leave-one-out cross-validation were 56.2%, 85.9%, and 98.3% at 5%, 10%, and 20%contamination levels, respectively. Solvent extraction optimization, we found that a mixture of 40–50% methanol, 30–50% dichloromethane, and 10–20% water was most efficient for the analysis of the flavonoid patterns in the six plant systems under investigation. Conclusion: Concerning the extraction optimization, a universal solvent could not be defined exactly by response surface methodologies as reported in similar studies involving different analytical platforms (mostly highperformance liquid chromatography) but suggestions for near-optimal solvent compositions with competitive performances compared to pure and 70% methanol could be made.